39 Bakers: dilemma in expansion (part A). Issue 4 (26th November 2021) - Kumar, Jitender; Tapar, Archit Vinod
Abstract : Subject area: Retail marketing: it can be discussed in a retail marketing course to explain the growth and expansion of the retail chain and illustrate the features of a retail model that can consider franchise as a method to expand or distribute its branded merchandise in other retail outlets. The case will also help assess the financially viable growth. Marketing Management: It can be useful for a comprehensive yet straightforward explanation of marketing mix price, promotion, place, and product, also at the same time it serves to explain the importance of customer service in terms of retailing. Strategic Marketing: The case provides varied growth options that are being considered by retail organizations, which gives the student real-time opportunity to arrive at strategic decisions by considering financial viability, internal strengths (SWOT analysis), franchising as a growth option. Study level/applicability: This case can be used in foundation course on retail marketing or even in strategic marketing in postgraduate management program, or the dilemma can be explained as a part of a marketing course for postgraduate, executive programs, management development programs. Case overview: Kanwar, the owner of 39 Bakers, was one of the fastest-growing retail outlets in Jammu, India. He had been successful in carving his pie for himself with its unique bakery products of more than 1000 variety of, break-even point price, everyday surprise product (EDSP), reasonable price, open kitchen concept, hygiene, excellent customer service. Within three years, 39 Bakers had grown from one to eight outlets, and revenue had increased to US$68, 621, and vision was to achieve US$2m within the next three years. To achieve his vision, he made two business expansion plans either to start product distribution to other retailers like an FMCG company or to go ahead with the business format franchising model. The investors needed a detailed planned within three days. But Kanwar had to decide should he expand geographically and start with franchise model or shall he establish his brand with product distribution, and then go for the franchise model, which plan would make him reach his vision by 2023? Which strategy would be efficient? He indeed wanted to go for the franchise model, but the question is when? Expected learning outcomes: This case will help entrepreneurs to decide on services and retail industries to expand their business and explore available growth options. It offers a platform to talk about how often franchising used to fuel growth. Either you select to be a franchisee or independent business owner or provide franchising opportunities or start your distribution network, a detailed business plan is one of the most critical decision-making activities. Without adequate details, it can make your life's most expensive option. After students have worked on the case and the task questions, the students can analyze whether a company should grow through product distribution, franchise or both; appreciate the significance of a business plan and to recognize all aspects of a retail operation, including the marketing mix; carry out strengths, weakness, opportunities, threats analysis and can develop Internal and External Factor Evaluation Matrix (IFE AND EFE); and examine various franchise options available for business expansion in a developing econ. Complexity academic level: Position in course – This case can be used in foundation course on retail marketing or even in strategic marketing in postgraduate management program, or the dilemma can be explained as a part of a marketing course for postgraduate, executive programs and management development programs. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS: 8 Marketing.